Analisis Risiko K3 dengan Metode HIRARC di PT X - Johan Kusuma; Kriswanto Widiawan (Jurnal Titra, 2021)
PT X is a manufacturing company that produce healthcare product such as medicated and non-medicated plaster. The company do not have occupational health and safety division yet, so there was several dangerous accident that have occurred. Risk analysis is carried out to detect potential risk before accident happened. Risk analysis hopefully could make a sense of security and comfort for the employees that work there. The research begins with a literature study on HIRARC, company observations, hazard identification, risk assessment, then risk control. Risk control will be validated first by the company. If it is valid then an assessment will be carried out to see the estimated reduction of risk value after the risk control is implemented. The result of risk analysis is that, there are several potential hazards in the poduction area. The potential divided into 10 mild potential, 13 moderate potential, 6 significant potential, and 2 high risk potential. Risk controls are designed using risk control hierarchy that is elimination, substitute, technical design, administrative engineering, and personal protective equipment (PPE). After risk control is done, the risk reduction forecast is moderate potential become 1, significant potential become 3, and high risk potential is none.